A study on indoor air quality at the stadiums / Muhammad Iqkram Munawwar Mohamad Nasser - Mohamad Nasser, Muhammad Iqkram Munawwar (Faculty of Architecture, Planning and Surveying, 2014)
In modem day, people mostly adult living in indoor compare to outdoor due to working purposed. A result of a research from cdc.gov, 2014 indicate that people spent about 90% of their time indoor. The research also indicate that the air inside a building is more polluted compare to outdoor air. The problems arise when these indoor air quality affect the health of the occupants health. Therefore, three indoor stadiums building was studied in this research. In this studies, three factor of indoor air quality is being focused which are humidity, temperature and air velocity. By using appropriate equipment which is velocicalc meter, the air indoor in the selected indoor stadiums of case study building will be tested. Other than that, an interview to the maintenance of the stadiums will be conducted to get more information about the IAQ in the selected indoor stadiums. Finally, the data collected will be analyzed. The finding from the study shows value of humidity, temperature and air velocity in each case study indoor stadiums are in satisfaction condition whereby each indoor stadiums show value of air velocity does not reach the standards set, while the humidity is slightly highest compare the permissible value from DOSH. Thus, proper conclusion and recommendation will be provided to overcome the indoor air quality problems in the future.